A comprehensive overview of focused ion beam-scanning electron microscopy (FIB-SEM) applications for the evaluation of outer retina - Ch, Sanjay; Lim, Rayne R.; Low, Shermaine W. Y.; Grant, Deana G.; Patterson, Sam; Ramasubramanian, Aparna; Gadicherla, Ashish K.; Chaurasia, Shyam S. (Frontiers in Cell and Developmental Biology, 2025)
The retina is the light-sensitive inner layer of the eye, consisting of multiple cell types organized into ten distinct layers of neurons interconnected by synapses that play a crucial role in visual function. Any pathological alterations in this intricate structure can lead to vision impairment. Conventional electron microscopy techniques, including scanning electron microscopy (SEM) and transmission electron microscopy (TEM), provide our current understanding of ultrastructural defects in the retina. However, they are limited by their inability to image the complex three-dimensional (3D) structure layer-by-layer at a nanoscale resolution. Advanced electron microscopy techniques, including serial block face scanning (SBF), have emerged as a superior alternative to traditional imaging methods for enhancing the understanding of 3D segmentation at the nanoscale and revealing the ultrastructural architecture of the retina under both physiological and pathological conditions. This article provides a comprehensive overview of the advancements in SBF electron microscopy, emphasizing focused ion beam (FIB)-SEM for studying the interdigitation zone (IZ), which connects the cone outer segments to the retinal pigment epithelium (RPE) to enhance the understanding of retinal degenerative diseases such as inherited retinal disorders (IRDs), age-related macular degeneration (AMD), and diabetic retinopathy (DR). We have collated and discussed current literature alongside our recent work on FIB-SEM applications, particularly in examining the structural integrity of the outer retina. FIB-SEM can bridge the knowledge gap between structural insights and functional impairments through its state-of-the-art imaging and 3D segmentation capabilities. Additionally, it offers various applications for the pathological evaluation of retinal degenerative diseases.